Identifying solution strategies in a mental-rotation test with gender-stereotyped objects by analyzing gaze patterns - Mirko Saunders; Claudia Michaela Quaiser-Pohl (Bern Open Publishing, 2021)
Many studies deal with solution strategies in mental-rotation tests. The approaches range from global analysis, attention to object parts, holistic and piecemeal strategy to a combined strategy. Other studies do not speak of strategies, but of holistic or piecemeal processes or even of holistic or piecemeal rotation. The methodological approach used here is to identify mental-rotation strategies via gaze patterns derived from eye-tracking data when solving chronometric mental-rotation tasks with gender-stereotyped objects. The mental-rotation test consists of 3 male-stereotyped objects (locomotive, hammer, wrench) and 3 female-stereotyped objects (pram, hand mirror, brush) rotated at eight different angles. The sample consisted of 16 women and 10 men (age: M=21.58; SD=4.21). The results of a qualitative analysis with two individual objects (wrench and brush) showed four different gaze patterns. These gaze patterns appeared with different frequency in the two objects and correlated differently with performance and response time. The results indicate either an object-oriented or an egocentric mental-rotation strategy behind the gaze patterns. In general, a new methodological approach has been developed to identify mental-rotation strategies bottom-up which can also be used for other stimulus types.